SMEs growth and profitability, productivity and debt relationships - Zélia Serrasqueiro; Beatriz Pinto; Filipe Sardo (Journal of Economics, Finance and Administrative Science, 2023)
Purpose - This study aims to seek to analyse the relationships between profitability, productivity, external debt and growth in SMEs. The authors also analyse firm size and age as explicative variables of small and medium-sized enterprise (SME) growth. Design/methodology/approach In this paper the data were collected for 3309 SMEs for the period 2010-2019. The authors estimate the model using the system generalised method of moments dynamic estimator. Findings The results show that after a certain level of profitability, this determinant positively impacts SME growth. Productivity influences positively the firm growth. There is a positive effect of external debt on SME growth, which can be explained by the insufficiency of internally generated funds. The authors obtained a negative signal between size and firm growth, contradicting Gibrat's Law (1931). Moreover, the results suggest that SMEs grow less after a certain age, suggesting that small firms grow less after reaching the minimum scale of efficiency. Practical implications For SME owner-managers, this study enhances the importance of profitability and labour productivity for firm growth. For policymakers, the results suggest the need for favourable conditions for SMEs in accessing external finance. Originality/value Profitability negatively impacts on SME growth. However, the authors found that above a certain level of profitability, probably, as firms accumulate retained earnings, profitability has a positive effect on SME growth. Moreover, this study shows that labour productivity and debt positively impact on SME growth, evidencing the importance of the availability of financial resources to sustain the growth of these firms.
Keywords: G32; 330; Debt; Growth; Productivity; Profitability; SMEs